Разведки северо-восточной оконечности Керченского полуострова - Бейлин, Д.В.; Куликов, А.В.; Бейлина, С.А. (Археологічні дослідження в Україні, 2010)
In 2009, the Prospecting Group of the Kerch Complex Expedition conducted archaeological prospecting and trenching in the north-eastern part of the Kerch Peninsula. The sites not known before were discovered and mapped, new information was obtained regarding stratigraphy of cultural layers, chronology and topography of the burial grounds, necropolei and settlements of the Late Bronze epoch, Ancient and Mediaeval periods.